Effect of photodynamic therapy in combination with mitomycin C on a mitomycin-resistant bladder cancer cell line. - Datta, S. N. (Nature Publishing Group, 1997)
Photodynamic therapy is a method for treating cancer using drugs activated by light. A new compound, 5-aminolaevulinic acid (ALA), is a precursor of the active photosensitizer protoporphyrin IX (PpIX) and has fewer side-effects and much more transient phototoxicity than previous photosensitizers. Cell survival of ALA-mediated photodynamic therapy was measured in the J82 bladder cancer cell line, along with its mitomycin C-resistant counterpart J82/MMC. This demonstrated that mitomycin resistance is not cross-resistant to photodynamic therapy. There was also a suggestion that the mitomycin-resistant cells were more susceptible to photodynamic therapy than the parent cell line. Photodynamic therapy appeared to enhance the effect of mitomycin C, when mitomycin C was given first. This phenomenon was apparent for both drug-resistant and drug-sensitive cell lines. This suggests a possible role for combined mitomycin C and photodynamic therapy in superficial bladder tumours that have recurred despite intravesical cytotoxic drug treatment.